A within-host model on the interaction dynamics between innate immune cells and Mycobacterium tuberculosis - Eduardo Ibargüen-Mondragón; M. Victoria Otero-Espinar; Miller Cerón Gómez (Mathematical Biosciences and Engineering)
Tuberculosis is the leading cause of death worldwide from a single infectious agent; it has also been declared a threat to humanity by the World Health Organization. New insights indicate that the innate immune response plays a crucial role in determining the outcome of the infection. In this study, we assessed the role of macrophages in the innate immune response through a simple mathematical model. Our results confirm that macrophages provide the primary protective response against Mycobacterium tuberculosis. However, they also highlight the importance of other innate cells in the outcome of infection. Specifically, our findings suggest that, in addition to macrophage activity, the involvement of other innate immune cells is essential for eliminating or controlling bacterial progression, ultimately leading to an adaptive immune response.